Estudio de la dinámica de la relación comercial entre Colombia y Brasil en los periodos comprendidos de 2002-2013 (2015)
In this graduation project has aimed to analyze the dynamics of trade relations between Colombia and Brazil in the period between 2002-2013, determined through the description of the development of the foreign policy of each country concerned, and the evolution of the relationship in this period of time. A descriptive methodology of longitudinal non-experimental order for the period to which correspond the data is used. In keeping with this, the results corresponded to the effects of the ACE agreement No. 59 which evidenced the intensification of exports and imports CAN, Mercosur and specifically Brazil, corresponding to an increase in the trade balance and an increase in rates of foreign direct investment. So it is concluded that complementation Can - Mercosur agreement generates positive results consistent with its fundamental purpose of integration and regional complementation, afforded a scenario of opportunities for expansion and diversification of the export supply, by means of trade policies that achieve real benefit of investment and regional development approaches